Emisión γ de supervientos galácticos - Kornecki, Paula (2020)
Star-forming galaxies are the first extragalactic γ-ray sources whose emission comes mostly fromphenomena linked to their stellar populations. The strongest evidence suppoting this interpretation is the quasi-linear correlation between their γ-ray luminosities and their star formation rates, observed by the Fermi mission.Recently, it has been proposed that the γ-ray emission of one of these galaxies (NGC 253) could be explained bythe interaction of relativistic particles, accelerated in its galactic superwind, with radiation fields and surroundingmatter. In this work we extend this model to galaxies with different star formation rates, and explore its abilityto explain the aforementioned correlation. We find that the model pedicts a change in the slope of the correla-tion, contrary to those in which the emission comes from the disk. Although the model describes the observedluminosities in order of magnitude, the trend is at most marginally consistent with observations.